Doxycycline for community treatment of suspected COVID-19 in people at high risk of adverse outcomes in the UK (PRINCIPLE): a randomised, controlled, open-label, adaptive platform trial. Issue 9 (September 2021) - Butler, Christopher C; Yu, Ly-Mee; Dorward, Jienchi; Gbinigie, Oghenekome; Hayward, Gail; Saville, Benjamin R; Van Hecke, Oliver; Berry, Nicholas; Detry, Michelle A; Saunders, Christina; Fitzgerald, Mark; Harris, Victoria; et al.
Summary: Background: Doxycycline is often used for treating COVID-19 respiratory symptoms in the community despite an absence of evidence from clinical trials to support its use. We aimed to assess the efficacy of doxycycline to treat suspected COVID-19 in the community among people at high risk of adverse outcomes. Methods: We did a national, open-label, multi-arm, adaptive platform randomised trial of interventions against COVID-19 in older people (PRINCIPLE) across primary care centres in the UK. We included people aged 65 years or older, or 50 years or older with comorbidities (weakened immune system, heart disease, hypertension, asthma or lung disease, diabetes, mild hepatic impairment, stroke or neurological problem, and self-reported obesity or body-mass index of 35 kg/m 2 or greater), who had been unwell (for ≤14 days) with suspected COVID-19 or a positive PCR test for SARS-CoV-2 infection in the community. Participants were randomly assigned using response adaptive randomisation to usual care only, usual care plus oral doxycycline (200 mg on day 1, then 100 mg once daily for the following 6 days), or usual care plus other interventions. The interventions reported in this manuscript are usual care plus doxycycline and usual care only; evaluations of other interventions in this platform trial are ongoing. The coprimary endpoints were time to first self-reported recovery, and hospitalisation or death related to COVID-19, both measured over 28 days from randomisation and analysed by intention to treat. This trial is ongoing and is registered with ISRCTN, 86534580. Findings: The trial opened on April 2, 2020. Randomisation to doxycycline began on July 24, 2020, and was stopped on Dec 14, 2020, because the prespecified futility criterion was met; 2689 participants were enrolled and randomised between these dates. Of these, 2508 (93·3%) participants contributed follow-up data and were included in the primary analysis: 780 (31·1%) in the usual care plus doxycycline group, 948 in the usual care only group (37·8%), and 780 (31·1%) in the usual care plus other interventions group. Among the 1792 participants randomly assigned to the usual care plus doxycycline and usual care only groups, the mean age was 61·1 years (SD 7·9); 999 (55·7%) participants were female and 790 (44·1%) were male. In the primary analysis model, there was little evidence of difference in median time to first self-reported recovery between the usual care plus doxycycline group and the usual care only group (9·6 [95% Bayesian Credible Interval [BCI] 8·3 to 11·0] days vs 10·1 [8·7 to 11·7] days, hazard ratio 1·04 [95% BCI 0·93 to 1·17]). The estimated benefit in median time to first self-reported recovery was 0·5 days [95% BCI −0·99 to 2·04] and the probability of a clinically meaningful benefit (defined as ≥1·5 days) was 0·10. Hospitalisation or death related to COVID-19 occurred in 41 (crude percentage 5·3%) participants in the usual care plus doxycycline group and 43 (4·5%) in the usual care only group (estimated absolute percentage difference −0·5% [95% BCI −2·6 to 1·4]); there were five deaths (0·6%) in the usual care plus doxycycline group and two (0·2%) in the usual care only group. Interpretation: In patients with suspected COVID-19 in the community in the UK, who were at high risk of adverse outcomes, treatment with doxycycline was not associated with clinically meaningful reductions in time to recovery or hospital admissions or deaths related to COVID-19, and should not be used as a routine treatment for COVID-19. Funding: UK Research and Innovation, Department of Health and Social Care, National Institute for Health Research.